Robotics, mechatronics and manufacturing systems : transactions of the IMACS/SICE International Symposium on Robotics, Mechatronics, and Manufacturing Systems, Kobe, Japan, 16-20 September, 1992 - Takamori, Toshi, 1940-; Tsuchiya, Kazuo, 1943- (North-Holland : IMACS, 1993)
One of the most important problems in the field of engineering and technology is the development of so-called <Q>intelligent systems</Q>, which can perform various intellectual tasks. This book is dedicated to the current progress of research in this vast field and specifically explores the topics of robotics, mechatronics and manufacturing systems.